Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Hindu dan Budi Pekerti Pada Jenjang SMP di Kabupaten Bangli - Sutriyanti, Ni Komang; Luwih, I Made; Suandewa, I Gusti Lanang Agung (Jayapangus Press, 2024)
Education is one aspect of life that receives extra attention for the progress of a nation. Indonesia is no exception, which is currently still making great efforts to improve the quality of its education. One of the efforts that has been made by Indonesian people is to implement a new curriculum called Merdeka Curriculum. However, as long as its existence, there were still many schools and teachers who need guidelines to implement it optimally. Based on these problems, it was very appropriate to conduct a study with the title Implementation of the Independent Curriculum in Learning Hindu Religious Education and Ethics at the Junior High School level in Bangli Regency. The aim of this research was to describe the implementation of Merdeka Curriculum in the learning planning stage, learning implementation stage, and learning evaluation stage. Through qualitative research methods with a descriptive naturalistic approach. The results of the research showed that, firstly, at the learning planning stage, the form of implementation of the Merdeka curriculum is carried out in several ways, including: 1) Holistic deepening of Merdeka curriculum, 2) Selection of the independent option to change as a reference for Merdeka curriculum, 3) Preparation of teaching modules based on Merdeka curriculum , 4) Preparing a variety of teaching materials, 5) Preparing a variety of learning media, and 6) Designing formative and summative assessments. Second, at the learning implementation stage, the implementation of Merdeka Curriculum is carried out in several ways, including: 1) Providing initial diagnostic assessments to determine student diversity, 2) Implementing differentiated learning, 3) Applying the Project Based Learning (PjBL) learning model, and 4) Application of Problem Based Learning (PBL) and Discovery Learning (DL) learning models. And thirdly, at the learning evaluation stage, the form of implementation of the Merdeka curriculum is carried out by implementing a combination of formative and summative assessments.